University of North Texas Press: 1990 to 2000. (Texas Folklore Society (1971-2000), 2000)
The chapter discusses the events that transpired in the Texas Folklore Society from 1990 to 2000. The society entered the last decade of the 20th century with a new secretary-assistant editor, Carolyn Satterwhite, a new publisher, Fran Vick of the University of North Texas Press and total cash assets of $112,655.25. The society's move to the University of North Texas Press was easy and comfortable because the society had worked with Fran Vick and E-Heart Press for four publications from 1979 to 1983.